Oral Intubation Attempts in Patients With a Laryngectomy: A Significant Safety Threat. (May 2021) - Brenner, Michael J.; Cramer, John D.; McGrath, Brendan A.; Balakrishnan, Karthik; Stepan, Katelyn O.; Pandian, Vinciya; Roberson, David W.; Shah, Rahul K.; Chen, Amy Y.; Brook, Itzhak; Nussenbaum, Brian
It is impossible to secure the airway of a patient with "neck-only" breathing transorally or transnasally. Surgical removal of the larynx (laryngectomy) or tracheal rerouting (tracheoesophageal diversion or laryngotracheal separation) creates anatomic discontinuity. Misguided attempts at oral intubation of neck breathers may cause hypoxic brain injury or death. We present national data from the American Academy of Otolaryngology–Head and Neck Surgery, the American Head and Neck Society, and the United Kingdom's National Reporting and Learning Service. Over half of US otolaryngologist respondents reported instances of attempted oral intubations among patients with laryngectomy, with a mortality rate of 26%. UK audits similarly revealed numerous resuscitation efforts where misunderstanding of neck breather status led to harm or death. Such data underscore the critical importance of staff education, patient engagement, effective signage, and systems-based best practices to reliably clarify neck breather status and provide necessary resources for safe patient airway management.